Count your blessings as Malaysians - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
WHILE Malaysia and its diverse population celebrates Eidul Fitri peacefully across all cultures and beliefs, different countries have different stories to tell. Some are not so lucky as in the case of Sudan where talks over a transition to civil government turned bloody. Libya was still gunning for Tripoli, and migrants from other war-torn countries continued to suffer especially women and children. The lessons of Ramadan seem to have trickled down very little in saving humanity as it is intended to do.